THE INTERVIEW AFTER AN OBSERVED LESSON AS A PLACE FOR DEVELOPING TRAINING PRACTICES - Marianne Jacquin (Babylonia, 2019)
The action research (AR) presented in this article was conducted as part of the 2016-2019 program of the European Centre for Modern Languages in Graz, and specifically within the "Action Research Community for Language Teachers" project at the University Institute for the Formation of Teachers (IUFE) in Geneva. The focus was on the feedback given by the teaching assistant to interns after an observed lesson. The goal is to identify discursive strategies that stimulate self-reflection and analysis among the participants in a constructive way.